A Salivary Endo-β-1, 4-Glucanase Acts as an Effector That Enables the Brown Planthopper to Feed on Rice. Issue 3 (26th January 2017) - Ji, Rui; Ye, Wenfeng; Chen, Hongdan; Zeng, Jiamei; Li, Heng; Yu, Haixin; Li, Jiancai; Lou, Yonggen
Abstract : A salivary endo-β-1, 4-glucanase in the rice brown planthopper Nilaparvata lugens facilitates access to the phloem by degrading celluloses in plant cell walls. Abstract: The brown planthopper (BPH ) Nilaparvata lugens is one of the most destructive insect pests on rice ( Oryza sativa ) in Asia. After landing on plants, BPH rapidly accesses plant phloem and sucks the phloem sap through unknown mechanisms. We discovered a salivary endo-β-1, 4-glucanase (NlEG1) that has endoglucanase activity with a maximal activity at pH 6 at 37°C and is secreted into rice plants by BPH . NlEG1 is highly expressed in the salivary glands and midgut. Silencing NlEG1 decreases the capacity of BPH to reach the phloem and reduces its food intake, mass, survival, and fecundity on rice plants. By contrast, NlEG1 silencing had only a small effect on the survival rate of BPH raised on artificial diet. Moreover, NlEG1 secreted by BPH did not elicit the production of the defense-related signal molecules salicylic acid, jasmonic acid, and jasmonoyl-isoleucine in rice, although wounding plus the application of the recombination protein NlEG1 did slightly enhance the levels of jasmonic acid and jasmonoyl-isoleucine in plants compared with the corresponding controls. These data suggest that NlEG1 enables the BPH 's stylet to reach the phloem by degrading celluloses in plant cell walls, thereby functioning as an effector that overcomes the plant cell wall defense in rice.